Answer:
Explanation:
(a) In order to use the elimination method, multiply the second equation by 2.
It becomes 2x + 4y = 20.
Subtract that from the first equation: 3x + 4y = 12
3x + 4y - 2x - 4y = 12 - 20
x = -8
Put that back in the second equation: -8 + 2y = 10
2y = 18
y = 9
(b) In order to use the substitution method, subtract 2y from the second equation.
It becomes x + 2y - 2y = 10 - 2y
x = 10 - 2y
Substitute that into the first equation:
3(10 - 2y) + 4y = 12
30 - 6y + 4y = 12
30 - 2y = 12
2y = 18
y = 9
Put back into the equation for x:
x = 10 - 2(9)
= 10 - 18
= -8